Determinants of knowledge, attitudes and childbirth experiences related to obstetric violence among women who delivered in the public health facilities of Jimma Zone Southwest Ethiopia: A cross sectional study design - Ayanos Taye; Tefera Belachew (PLoS ONE, 2026)
Background The World Health Organization recognizes every woman has the right to respectful and dignified care during childbirth. However, a significant number of women experienced obstetric violence (OV) acts or omissions causing harm, violating rights, or undermining autonomy, remains prevalent globally, including in Ethiopia where women’s knowledge gaps and unfavorable attitudes perpetuate it due to limited rights awareness and cultural norms. In southwest Ethiopia, evidence on women’s knowledge, attitudes, childbirth experience related to OV, and their determinants among facility-based deliveries is scarce. This study thus investigates these factors among mothers delivering in public health facilities. Method An institutional-based retrospective cross-sectional study was conducted among 402 women in public hospitals of the Jimma zone from August 12 to October 12, 2022. A simple random sampling technique was used to select the study subjects for structured, pre-tested face-to-face exit interviews. Data were entered into Epi-Data version 3.1 and exported to SPSS version 23 for analysis. Then, factors that showed significant associations in a bivariable linear regression model were added to multivariable linear regression models. Variables that had a P-value of < 0.05 in the multivariable model were considered statistically significant. Finaly, the results were presented using texts, tables and graphs. Results The present study showed that more than two-thirds of women had a knowledge about universal rights during childbirth with a mean score of 14.89 ± 6.76, 68). About two out of three participants had unfavorable attitude towards childbirth experience (mean 33.55 ± 4.91, 66%) and experienced OV (mean 67.09 ± 11.79, 64%) during labor and childbirth. Women living in urban areas (β = −4.69, 95% CI: −6.41, −2.96), those with antenatal care (ANC) contacts (β = −9.65, 95% CI: −11.18, −8.11), who gave birth at night (β = 4.06, 95% CI: 2.42, 5.70), and without obstetric complications (β = −8.07, 95% CI: −9.98, −6.16) showed significant associations with obstetric violence. ANC contacts (β = 3.23, 95% CI: 2.02, 4.45) and companion utilization (β = 4.87, 95% CI: 2.14, 7.59) positively associated with women’s knowledge levels. Absence of obstetric complications (β = −3.06, 95% CI: −4.00, −2.11), urban residence (β = −1.89, 95% CI: (−2.86, −1.01) and ANC contacts (β = −3.36, 95% CI: −4.13, −2.59) were associated with unfavorable attitudes toward childbirth experience related to obstetric violence. Conclusion The study revealed that more than two-thirds of participants had relatively lower knowledge of childbirth rights. Likewise, approximately two-thirds held unfavorable attitudes and experienced obstetric violence (OV). The most commonly reported forms OV were non-dignified care, non-consented care, and physical abuse. Sociodemographic factors (residence, maternal occupation) and maternal factors (ANC contacts, obstetric complications, companion utilization) associated with women’s knowledge, attitudes, and childbirth experience related to OV. To mitigate the challenges, prioritize comprehensive training for providers on respectful and dignified care, alongside women’s education to foster rights awareness and self-advocacy. Enhance ANC access, companion policies, and targeted strategies for high-risk groups (e.g., rural residents, certain occupations) to create supportive childbirth environments.